Development and Testing of an IoT-Based Yogurt Fermenter Prototype for MSMEs - Septian Deny Widya Putra; Nuri Andarwulan; Dede Robiatul Adawiyah (JST (Jurnal Sains dan Teknologi), 2026)
Temperature is an important parameter in the yogurt fermentation process. MSME-scale yogurt fermenters currently available do not yet have an accurate temperature-control system. This study aims to develop an Internet of Things (IoT)-based yogurt fermenter prototype with a temperature-control system using the PID method. PID parameter determination was carried out using the modified Ziegler-Nichols and Chien-Hrones-Reswick tuning methods. The evaluation results showed that the PID parameters obtained from the Ziegler-Nichols method provided better temperature control performance than those from the CHR method, with lower rise time, settling time, and overshoot. The 8-hour fermentation test showed that the average fermenter temperature approached the target of 45°C, with minimal deviation. Increasing the fermentation temperature and adding rice flour increased the rate of pH decrease. This study shows that a PID-based control system can significantly improve the performance of MSME-scale yogurt fermenters, thereby increasing the competitiveness of the MSME-scale yogurt industry. This system implies that, in addition to being used as a yogurt fermenter, it can also serve other functions because it is essentially a water bath.